The Lecturers’ English Ability Through the Toefl Test - Dian Susyla; Ria Angraini; Ririn Putri Ananda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine and describe lecturers' English language skills, which can be seen through the TOEFL test. This research method is descriptive qualitative. The researcher gave a TOEFL-like test to 109 lecturers as research subjects. TOEFL ability is mapped into the Common European Framework of Reference for Language (CEFR), measured at four different levels, namely A2, B1, B2, and C. The results show that no lecturer has C1 ability in the Listening section. Two lecturers are at level B2, 12 people are at level B1, and the remaining 95 people are at level A2. The average for Listening is in the A2-SD level category. For Structure and Written Expression, only four lecturers are at level B2; 25 at B1 level; and 80 at level A2. The average for SWE is 40 in the A2 elementary level category. As for the Reading section, only one lecturer is at level C1; 2 at level B2; 6 at level B1; 98 at level A2. The average score for Reading is in the A2-SD level category. In conclusion, most of the lecturers' English skills (Listening, Structure and Writing Expression, and Reading) are still very weak. Keywords: Lecturers’ English Ability, TOEFL